Screening for vitamin D deficiency in a tropical area: results of a sun exposure questionnaire - Fernanda Barros Bittar (BMC Endocrine Disorders, 2018)
Abstract Background Vitamin D deficiency is pandemic while resources available to measure 25-hydroxyvitamin D (25OHD) are limited. The present study aimed to verify whether sun exposure measured by a structured questionnaire could predict serum 25OHD concentrations in healthy Caucasian individuals living in a tropical area. Methods A cross-sectional study was carried out in subjects living in the greater São Paulo area, Brazil. Two groups of 50 young (20 to 40 years old) and 50 older (60 to 80 years old) subjects (N = 200) answered a structured questionnaire on sun exposure and had blood samples drawn for serum 25OHD concentration measurement during both summer and winter. Anthropometric data were also recorded. Correlation between the questionnaire variables (duration of sun exposure, amount of exposed skin, total sun exposure score - TSES and other data) and serum 25OHD concentration was evaluated. Results Mean serum 25OHD concentration was 17.60 ± 7.3 ng/mL with no difference between age groups (p = 0.293). TSES weakly correlated with serum 25OHD levels (r = 0.264; p < 0.001). Separate analyzes by age groups demonstrated that TSES correlated significantly with serum 25OHD concentration only in the older subjects during summer (r = 0.322; p = 0.023). Using linear regression analyses, TSES and body mass index (BMI) were significantly associated with serum 25OHD levels. On the other hand, Receiver operating characteristic (ROC) analysis for TSES showed no significance as a screening tool for vitamin D deficiency (p = 0.172). Conclusion Sun exposure questionnaire associated with BMI correlates with serum 25OHD concentration with very low accuracy. The use of the questionnaire does not discriminate between vitamin D sufficient and deficient individuals.